Pengaruh Penggunaan Gadget Terhadap Perkembangan Sosial Anak Pra Sekolah Di Kabupaten Pesawaran Lampung - Sulistiawati, Yuni; Supratman, Vida Artha; Nugroho, Tri Adi (Wellness And Healthy Magazine, 2019)
The development of communication technology today brings many social changes. Not only changes in mindset in addressingsomething, but also has an impact on changing behavior socially. Changes that occur are not always positive because on the other hand it also has a negative effect on users. This condition isespecially true for children who are unable to filter negative impacts such as lack of social interaction with the environment so that there are delays in social development, Social development is defined as the process of learning to conform to group norms, morals, and traditions, merged into a single communicating and working together. Results of Health Research (RISKESDAS) child development in 2018 it was reported that the social-emotional development of Indonesian children reached 69.9% lower when compared to Vietnam 91.2%,Vietnam countries, Kazakhstan 82.1%, 79.4% and Thailand. One of the factors or stimuli that can affect a child's social development, namely play habits of children in the gadget. The purpose of this study was to determine the effect of the use of gadgets to the social development of preschool children in kindergarten Bumi Agung subdistrict village Tegineneng Pesawaran District 2019. The research design used in this study is a comparative analytic approach. The population in this study is whole preschoolers in TK ABA Sidobasuki and children in TK Dharma Wanita Masgar with the number of 119 children. The sampling technique is purposive sampling 75 respondents from TK ABA Sidobasuki and from TK Dharma Wanita Masgar. This study bivariate analysis using Mann Whitney test. The results obtained by the majority of children who use gadgets have poor social development of 53.3% while the majority of children who don’t use gadgets of social development are good at 56.7%. The results were obtained p-value 0.049 (less than 0.05) which means there is the influence of the use of gadgets to the social development of preschool children in Kindergarten Village Caravan Pesawaran District Court District of Lampung Tegineneng 2019. Based on the results, it is advisable for parents to be more selective in giving the a toy to the child and the need for supervision as well as firmness in giving limits to children in a gadget play.